Loneliness at universities: determinants of emotional and social loneliness among students - Diehl, Katharina; Hilger-Kolb, Jennifer (International journal of environmental research and public health, 2018)
The transition from school to university is associated with social, structural, and behavioral changes. These changes may be related to feelings of loneliness, which are in turn related to morbidity. The authors’ aim was to quantify loneliness among students and to identify its determinants and its relation to transition-related variables (e.g., changes in weight, diet, or physical activity since the transition from high school to university). Coming from across Germany, 689 students participated in the Nutrition and Physical Activity in Adolescence (NuPhA) survey (16-29 years; 69.5% female). Associations of loneliness with the above-mentioned aspects were analyzed using descriptive statistics and linear regressions. Altogether, 32.4% felt moderately lonely and 3.2%, severely lonely. Emotional loneliness was more common than social loneliness (severe loneliness: 7.7% vs. 3.2%). Both were positively associated with feelings of depression and anxiety. Being married or in a committed relationship seemed to be protective factors for emotional loneliness. Physical inactivity, an immigrant background, and studying social sciences were related to higher social loneliness. Transition-related variables produced mixed results. In conclusion, this study's findings indicated that loneliness seemed to be prevalent in university students. The authors identified important starting points for interventions to prevent loneliness. Such interventions may help reduce the disease burden in the students' future professional life.